Islamic Philanthropy and Public Policy: A Study of Zakat Fatwas from the New Order Era to the Post-Reform Era - ., Moh. Mufid; Adamu Abubakar Muhammad (Jurnal Hukum Islam, 2023)
The ambiguity of the relationship between the state and religion in Indonesia causes the unique dynamics experienced by the legislative process of Islamic law in Indonesian laws and regulations. In this context, the Indonesian Ulama Council has a strategic position to encourage the legislative process of Islamic law into state law, including zakat norms. This paper discusses the legislation of Islamic philanthropic fatwas in state law that regulates zakat management in Indonesia, which is manifested in public policy. This research is normative research with a philosophical and historical approach. The research data used were the 22 fatwas of the Indonesian Ulama Council regarding zakat. The research results showed that Islamic philanthropic fatwa norms contribute significantly to public policy interventions that are oriented toward empowerment and community welfare improvement. This paper argues that the relationship pattern of the Indonesian Ulama Council's fatwa regarding zakat and positive law is as follows: first, sometimes a zakat fatwa strengthens state policies for the public benefit (ta'yīdī), and second, it becomes legal materials in formulating and making public policies (insyā'ī). Thus, the Islamic philanthropic fatwas of the Indonesian Ulama Council can become a tool of social control and a tool of social engineering for the Indonesian Muslim community.